Aging and the Haptic Perception of Material Properties. (December 2016) - Norman, J. Farley; Adkins, Olivia C.; Hoyng, Stevie C.; Dowell, Catherine J.; Pedersen, Lauren E.; Gilliam, Ashley N.
The ability of 26 younger (mean age was 22.5 years) and older adults (mean age was 72.6 years) to haptically perceive material properties was evaluated. The participants manually explored (for 5 seconds) 42 surfaces twice and placed each of these 84 experimental stimuli into one of seven categories: paper, plastic, metal, wood, stone, fabric, and fur/leather. In general, the participants were best able to identify fur/leather and wood materials; in contrast, recognition performance was worst for stone and paper. Despite similar overall patterns of performance for younger and older participants, the younger adults' recognition accuracies were 26.5% higher. The participants' tactile acuities (assessed by tactile grating orientation discrimination) affected their ability to identify surface material. In particular, the Pearson r correlation coefficient relating the participants' grating orientation thresholds and their material identification performance was −0.8: The higher the participants' thresholds, the lower the material recognition ability. While older adults are able to effectively perceive the solid shape of environmental objects using the sense of touch, their ability to perceive surface materials is significantly compromised.